Automated detection of repetitive focal activations in persistent atrial fibrillation: Validation of a novel detection algorithm and application through panoramic and sequential mapping. (14th October 2018) - Honarbakhsh, Shohreh; Schilling, Richard J.; Providencia, Rui; Keating, Emily; Sporton , Simon; Lowe, Martin; Lambiase, Pier D.; Chow, Anthony; Earley, Mark J.; Hunter, Ross J.
Abstract: Introduction: Identifying drivers in persistent atrial fibrillation (AF) remains challenging. We sought to validate an automated system for detection of focal activation using basket and PentaRay catheters in AF. Methods: Patients having ablation for atrial tachycardia (AT) and persistent AF were mapped. Thirty‐second unipolar basket and PentaRay recordings were analyzed using CARTOFINDER. Focal activation or "region of interest" (ROI) was defined as more than or equal to 2 consecutive focal activations with one electrode leading relative to its neighbors with QS morphology on the unipolar electrogram. ROI was validated in AT. AF patients were mapped to (1) look for evidence of focal activations on wavefront maps, (2) evaluate whether these were detected as ROI on basket recordings, and (3) whether these sites could be identified on sequential PentaRay recordings. Results: ROIs were identified in five focal ATs but none of 16 reentrant ATs. Twenty‐eight AF patients had 35 focal drivers identified from basket wavefront maps with an ablation response in all (16 cycle length slowing and 19 AF termination). Thirty focal activations were detected on basket ROI maps (86%). Twenty‐three of 28 patients had sequential PentaRay mapping and 22 of 30 focal drivers in these patients (73%) were identified as ROI. These drivers had greater temporal stability (3.6 ± 0.6 vs 2.7 ± 0.6; P  < 0.001), higher recurrence rate (12.4 ± 2.7 vs 7.2 ± 0.9; P  < 0.001), and more frequently were associated with AF termination ( P  < 0.001) compared with those not identified as ROI. Conclusions: Focal activations can be detected in AF using sequential recordings. The ablation response at focal sources suggests they may be viable therapeutic targets.